Changes in use of antidiabetic medications following price regulations in China (1999–2009). Issue 1 (7th January 2013) - Lu, Christine Y; Ross‐Degnan, Dennis; Stephens, Peter; Liu, Bao; Wagner, Anita K.
Abstract Background and Objectives Pharmaceutical expenditures are a major burden in China, partly because of pharmaceutical sales covering hospital operating costs, so a series of reductions in maximum retail prices of specific products, including antidiabetic medications, have been implemented. This is the first large‐scale, longitudinal study evaluating effects of two rounds of price regulations on use of antidiabetic medications. Methods We used quarterly purchasing data collected by IMS Health from more than 1000 hospitals in China (1999–2009). We used interrupted time‐series analysis to assess changes in the population‐adjusted market volume of insulin and oral hypoglycaemic products and in the percentage market share of price‐regulated products following price regulations implemented in December 2001 and December 2006. Results After the 2001 price regulation, there was a significant increase in market volume trend of insulin products (0.06 standard units/1000 population/quarter; 95% confidence interval: 0.04–0.08); utilisation of oral hypoglycaemic products remained stable. After the 2006 price regulation, there were significant increases in the market volume trend of both insulin products (0.18 standard units/1000 population/quarter; 0.12–0.23) and oral hypoglycaemic products (10.31 standard units/1000 population/quarter; 5.65–14.98). Market share of price‐regulated insulin and oral hypoglycaemic products did not change significantly after either price regulation. Conclusion Our results indicate that lowering the retail prices of specific products was associated with increases in total per capita utilisation of antidiabetic medications without shifts in use between non‐ and price‐regulated products. Broad volume increases suggest access to antidiabetic medications by additional people, increased use by those with prior access, or both.